The Black athlete as hero : American barrier breakers from nine sports - Dorinson, Joseph, 1936- (McFarland & Company, Inc., Publishers, 2022)
"Part history, part biography, this study examines the black athlete's search to unify what W.E.B. DuBois called the "two unreconciled strivings" of African Americans--the struggle to survive in black society while adapting to white society. Black athletes have served as vanguards of change, challenging the dominant culture, crossing social boundaries and raising political awareness. Champions like Joe Louis, Jackie Robinson, Muhammad Ali, Jim Brown, Wilma Rudolph, Roberto Clemente, Althea Gibson, Arthur Ashe, Serena Williams, Kareem Abdul-Jabbar and LeBron James make a difference, even as many in the black community question the idea of athletes as role models. The author argues the importance of sports heroes in a panic-plagued era beset with class division and racial privilege"--